Patient-reported outcomes in clinical practice - Sarah Dobrozsi; Julie A. Panepinto (2015)
Patient-reported outcome (PRO) measurement plays an increasingly important role in health care and understanding health outcomes. PROs are any report of a patient's health status that comes directly from the patient, and can measure patient symptoms, patient function, and quality-of-life. PROs have been used successfully to assess impairment in a clinical setting. Use of PROs to systematically quantify the patient experience provides valuable data to assist with clinical care; however, initiating use of PROs in clinical practice can be daunting. Here we provide suggestions for implementation of PROs and examples of opportunities to use PROs to tailor individual patient therapy to improve patient outcomes, patient-physician communication, and the quality of care for hematology/oncology patients.